Meropenem versus piperacillin-tazobactam for definitive treatment of bloodstream infections caused by AmpC beta-lactamase-producing enterobacter spp, citrobacter freundii, morganella morganii, providencia spp, or serratia marcescens: A pilot multicenter randomized controlled trial (MERINO-2) - Stewart, Adam G.; Paterson, David L.; Young, Barnaby; Lye, David C.; Davis, Joshua S.; Schneider, Kellie; Yılmaz, Mesut; Dinleyici, Rümeysa; Runnegar, Naomi; Henderson, Andrew; Archuleta, Sophia; Kalimuddin, Shirin; et al. (Oxford University Press, 2021)
Background: Carbapenems are recommended treatment for serious infections caused by AmpC-producing gram-negative bacteria but can select for carbapenem resistance. Piperacillin-tazobactam may be a suitable alternative. Methods: We enrolled adult patients with bloodstream infection due to chromosomal AmpC producers in a multicenter randomized controlled trial. Patients were assigned 1:1 to receive piperacillin-tazobactam 4.5 g every 6 hours or meropenem 1 g every 8 hours. The primary efficacy outcome was a composite of death, clinical failure, microbiological failure, and microbiological relapse at 30 days. Results: Seventy-two patients underwent randomization and were included in the primary analysis population. Eleven of 38 patients (29%) randomized to piperacillin-tazobactam met the primary outcome compared with 7 of 34 patients (21%) in the meropenem group (risk difference, 8% [95% confidence interval {CI},-12% to 28%]). Effects were consistent in an analysis of the per-protocol population. Within the subcomponents of the primary outcome, 5 of 38 (13%) experienced microbiological failure in the piperacillin-tazobactam group compared to 0 of 34 patients (0%) in the meropenem group (risk difference, 13% [95% CI, 2% to 24%]). In contrast, 0% vs 9% of microbiological relapses were seen in the piperacillin-tazobactam and meropenem arms, respectively. Susceptibility to piperacillin-tazobactam and meropenem using broth microdilution was found in 96.5% and 100% of isolates, respectively. The most common AmpC ?-lactamase genes identified were blaCMY-2, blaDHA-17, blaCMH-3, and blaACT-17. No ESBL, OXA, or other carbapenemase genes were identified. Conclusions: Among patients with bloodstream infection due to AmpC producers, piperacillin-tazobactam may lead to more microbiological failures, although fewer microbiological relapses were seen. Clinical Trials Registration: NCT02437045.
Meropenem versus piperacillin-tazobactam for definitive treatment of bloodstream infections caused by AmpC ?-Lactamase–producing enterobacter spp, citrobacter freundii, morganella morganii, providencia spp, or serratia marcescens: A pilot multicenter randomized controlled trial (MERINO-2)
Keywords: Ampc ?-Lactamase; Carbapenem; Clinical Trial; Enterobacterales; Piperacillin-Tazobactam